2022
DOI: 10.3390/healthcare10081499
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of GAITRite and the 10-m Walk Test to Measure Gait Speed in Adults with Chronic Ankle Instability

Abstract: Since there are many different assessments related to gait speed, it is important to determine the concurrent validity of each measure so that they can be used interchangeably. Our study aimed to investigate the concurrent validity of gait speed measured by the 10 m walk test (10 MWT) and the gold standard gait analysis system, the GAITRite system, for people with chronic ankle instability (CAI). For 16 people with CAI, 4 evaluations of the 10 MWT and 4 evaluations of the GAITRite system were performed (a comf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Our results verified that this simple, low-cost setup provides an excellent alternative in community settings in which sophisticated equipment, such as the GAITRite walkway, may not be available due to limitation of resources. Additionally, an earlier study reported that the manual stopwatch–footfall count method is comparable to a smart system [ 32 ], and our results are well aligned with earlier studies [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results verified that this simple, low-cost setup provides an excellent alternative in community settings in which sophisticated equipment, such as the GAITRite walkway, may not be available due to limitation of resources. Additionally, an earlier study reported that the manual stopwatch–footfall count method is comparable to a smart system [ 32 ], and our results are well aligned with earlier studies [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%